Current concepts in management of pain in children in the emergency department. - Krauss, Baruch S; Calligaris, Lorenzo; Green, Steven M; Barbi, Egidio (Lancet, 2016)
Pain is common in children presenting to emergency departments with episodic illnesses, acute injuries, and exacerbation of chronic disorders. We review recognition and assessment of pain in infants and children and discuss the manifestations of pain in children with chronic illness, recurrent pain syndromes, and cognitive impairment, including the difficulties of pain management in these patients. Non-pharmacological interventions, as adjuncts to pharmacological management for acute anxiety and pain, are described by age and development. We discuss the pharmacological management of acute pain and anxiety, reviewing invasive and non-invasive routes of administration, pharmacology, and adverse effects.
Keywords: Acute Pain; Analgesics, Opioid; Anesthetics, Local; Anti-Inflammatory Agents, Non-Steroidal; Anxiety; Child; Emergency Medicine; Emergency Service, Hospital; Humans; Pain Management; Pediatrics; Stress, Psychological